2021
DOI: 10.1007/s10029-021-02449-x
|View full text |Cite
|
Sign up to set email alerts
|

Early outcomes of component separation techniques: an analysis of the Spanish registry of incisional Hernia (EVEREG)

Abstract: Aim To analyze the outcomes of component separation techniques (CST) to treat incisional hernias (IH) in a large multicenter cohort of patients. Methods All IH repair using CST, registered in EVEREG from July 2012 to December 2019, were included. Data on the pre-operative patient characteristics and comorbidities, IH characteristics, surgical technique, complications, and recurrence were collected. Outcomes between anterior (ACS) and posterior component se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Larger cohort studies or data from national registries, varying from 184 to 3109 TAR cases, demonstrated slightly better outcomes than the smaller series: SSO 18–31%, SSE 19%, SSOPI 5-9% and recurrence 3-4% ( 6 , 10 , 18 , 19 , 50 , 51 ), which may be due to some learning curve effect.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Larger cohort studies or data from national registries, varying from 184 to 3109 TAR cases, demonstrated slightly better outcomes than the smaller series: SSO 18–31%, SSE 19%, SSOPI 5-9% and recurrence 3-4% ( 6 , 10 , 18 , 19 , 50 , 51 ), which may be due to some learning curve effect.…”
Section: Discussionmentioning
confidence: 82%
“…Major surgeries in an aging population maintain the surgical epidemic of incisional hernias (1,2). Repairing these hernias remains fraught with complications, especially if a patient need a component separation technique (CST) for primary fascial closure (3)(4)(5)(6). Such complex abdominal wall repair procedures can be challenging, require well-organized peri-operative multidisciplinary guidance and a team which should be able to adopt new techniques (7).…”
Section: Introductionmentioning
confidence: 99%
“…We do not routinely look for such a significant fascial dehiscence 1 month after surgery [ 33 ]. However, complex reconstructions can have recurrence rates as high as 10% after 6 months [ 34 ]. After 43 months, 94% of all fascial distances greater than 12 mm had developed a manifest hernia [ 22 ].…”
Section: Discussionmentioning
confidence: 99%